Is there a relationship between the playing position of soccer players and their food and macronutrient intake? - Iglesias-Gutierrez, E.; Garcia, A.; Garcia-Zapico, P.; Pérez-Landaluce, J.; Patterson, A. M.; Garcia-Roves, P. M. (Applied Physiology, Nutrition, and Metabolism, 2012)
Many authors have proposed the necessity of the design and implementation of dietary and nutrition education programs for soccer players, although little information is available about the determinants of food selection and nutrient intake. The aim of this study was to evaluate the nutritional intake and eating patterns of soccer players according to their playing position in the team. Eighty-seven young male soccer players (aged 16-21 years) were recruited from the junior teams of a Spanish First Division Soccer League Club and divided into 6 positional categories (goalkeepers, full-backs, centre-backs, midfielders, wingers, and forwards). Body composition (height, weight, and body fat), performance in soccer-specific tests (jumping, sprinting, and intermittent endurance), and dietary intake (weighed food intake method) were assessed. A spontaneous higher carbohydrate intake was observed for full-backs, midfielders, and wingers (g/kg body mass: 4.9 ± 1.0, 4.9 ± 1.3, 4.9 ± 0.8; % of energy intake: 47 ± 5, 46 ± 6, 46 ± 4), compared with goalkeepers and centre-backs (g/kg of body mass: 3.9 ± 1.0, 4.3 ± 1.1; % of energy intake: 44 ± 3, 42 ± 4). These differences were related to food selection patterns, and a higher contribution to daily energy intake of cereals, derivatives, and potatoes was observed between full-backs compared with goalkeepers and centre-backs (33% vs. 27% and 25%). The magnitude of these differences is limited considering the whole diet, and an inadequate nutrient intake were observed in most individuals of every group. The design and implementation of nutrition intervention programs, taking into consideration positional differences in nutritional intake, would be useful for these players.